HIV-PASS (Pain and Sadness Support): Randomized Controlled Trial of a Behavioral Health Intervention for Interference Due to Pain in People Living With HIV, Chronic Pain, and Depression. Issue 3 (3rd April 2023) - Uebelacker, Lisa A.; Pinkston, Megan M.; Busch, Andrew M.; Baker, Jason V.; Anderson, Bradley; Caviness, Celeste M.; Herman, Debra S.; Weisberg, Risa B.; Abrantes, Ana M.; Stein, Michael D.
ABSTRACT: Objective: This study aimed to determine whether HIV-Pain and Sadness Support (HIV-PASS), a collaborative behavioral health intervention based on behavioral activation, is associated with decreased pain-related interference with daily activities, depression, and other outcomes in people living with HIV. Methods: We conducted a three-site clinical trial ( n = 187) in which we randomly assigned participants to receive either HIV-PASS or health education control condition. In both conditions, participants received seven intervention sessions, comprising an initial in-person joint meeting with the participant, their HIV primary care provider and a behavioral health specialist, and six, primarily telephone-based, meetings with the behavioral health specialist and participant. The intervention period lasted 3 months, and follow-up assessments were conducted for an additional 9 months. Results: Compared with health education, HIV-PASS was associated with significantly lower pain-related interference with daily activities at the end of month 3 (our primary outcome; b = −1.31, 95% confidence interval = −2.28 to −0.34). We did not observe other differences between groups at 3 months in secondary outcomes that included worst or average pain in the past week, depression symptoms, anxiety, and perceived overall mental and physical health. There were no differences between groups on any outcomes at 12 months after enrollment. Conclusions: A targeted intervention can have positive effects on pain interference. At the end of intervention, effects we found were in a clinically significant range. However, effects diminished once the intervention period ended. Trial Registration: ClinicalTrials.gov NCT02766751.